Kemapuan Berpikir Matematis Siswa Berbasis Lesson Study Melalui Penerapan Alat Peraga - Etriana Meirista; Dian Mayasari (CV. Multi Kreasi Media, 2022)
Research on this observation was conducted to see how effective the use of teaching aids to improve student activity and learning outcomes in mathematics learning. The learning activity referred to here is how students can involve all psychophysical aspects, both physical and spiritual so that the acceleration of changes in their behavior can occur quickly, precisely, easily, and correctly, both related to cognitive, affective, and psychomotor aspects. The type of research used is Class Action Research (PTK). Observation was carried out as many as 2 cycles by giving essay questions as many as 5 numbers, with each cycle consisting of 2x30 minutes In general, each cycle starts from the stage of action planning, action execution, observation, and also reflection. Based on the results of this study, it shows that before using props, namely in cycle 1, student results were completed with an average percentage of 68.3% with KKM 78, while in cycle 2, props have been applied so that they were obtained with a completeness of 90.5% so that they experienced an increase of 22.2% with a moderate category in cycle 1 to a high category after being implemented in cycle 2. From these results, it can be seen that teaching aids are able to improve student learning outcomes which previously in cycle 1 student results had not reached the KKM score and after applying props in cycle 2 were able to improve student abilities effectively. The conclusion of the observations in this study is that the effectiveness of using teaching aids can improve student learning outcomes.